A theoretical study on the formation mechanism of carboxylic sulfuric anhydride and its potential role in new particle formation. Issue 9 (16th February 2022) - Zhang, Haijie; Wang, Wei; Li, Hong; Gao, Rui; Xu, Yisheng
Abstract : Organic acids could improve their nucleation ability through the cycloaddition reaction of SO3 to generate corresponding carboxylic sulfuric anhydrides which may play a potential role in the atmospheric new particle formation. Abstract : New particle formation (NPF) is the major source of atmospheric aerosol particles. However, the chemical species involved and the exact mechanism are still unclear. Cycloaddition reaction of SO3 to carboxylic acids bas been identified as a possible formation mechanism of carboxylic sulfuric anhydrides which may be involved in NPF. Herein, energy profiles for forming diaterpenylic acetate sulfuric anhydride (DTASA) through cycloaddition of SO3 to diaterpenylic acid acetate (DTAA) and the potential role of DTASA in NPF were studied through computational methods combined with atmospheric cluster dynamics code (ACDC). Gas phase reaction barriers for the two carboxyl groups of DTAA are 0.4 and 0.6 kcal mol −1, respectively, illustrating a feasible formation mechanism for DTASA. According to thermodynamical analysis and dynamical simulations, atmospheric clusters containing DTASA and atmospheric nucleation precursors sulfuric acid (SA), ammonia (NH3 ) and dimethylamine (DMA) possess both thermodynamically and dynamically higher stabilities than those of DTAA-contained clusters. Furthermore, DTASA–NH3 and DTASA–DMA are more stable than SA–NH3 and SA–DMA, enabling DTASA, even carboxylic sulfuric anhydrides, to become potential participants in the atmospheric NPF process which may hence promote a better understanding of NPF.